Pelatihan Mengolah Limbah Sapi menjadi Pupuk di Desa Nagasari, Kecamatan Serang Baru, Kabupaten Bekasi - Istianah Setyaningsih; Alfyyah Widad; Sri Mulyati; Wahid Dasa Ridwani (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2019)
Nagasari Village is one of the villages in Serang Baru Sub-district, Bekasi Regency, the majority of the population in this village as farmers and ranchers. The high number of people who have cattle in Nagasari village raises the problem for the village, namely the high number of cow dung waste. The confinement of knowledge both theoretically and practically related to the utilization of cow dung waste, causing the community to only dispose of and burn cow dung without exploiting it.  Based on the problem, we take the initiative to provide counseling and training on how to make organic fertilizer from cow dung. The process is done through socialization to the community, then conducted teaching on the method of implementing the implementation of the Hajj fertilizer from cow dung. The next step is the process of making and fermentation fertilizer. The results obtained by the enable will be applied to the community Tanamman and distributed or sold with organic fertilizer label Village.